Effects of environmental variation on beta diversity of semi-aquatic bugs in Amazonian streams influenced by bauxite extraction - Luz, Vinicius Araújo da; Cunha, Erlane José; Guterres, Alana Patricia Meguy; Pereira, Gizelia Ferreira Matos; Juen, Leandro (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2025)
Bauxite mining represents in the Amazon an economic activity with the potential to impact aquatic biodiversity. In this study, we evaluate the effects of environmental change in areas of bauxite mining and pasture on the diversity of semiaquatic insect communities in Amazonian streams. For this, we tested the following hypotheses: i) the environmental structure of streams will differ between different land uses and cover (pasture, mining and forest), ii) beta diversity (β) will be mainly affected by environmental variables related to habitat and riparian vegetation. Our results showed that the characteristics of the streams studied were not different between forest, pasture, and mining streams. On the other hand, the total beta diversity, and species replacement were associated with habitat variables, promoted by the environmental variation. Beta diversity in impacted streams was related to streams with greater widths and temperatures, while more preserved streams had greater canopy cover.. More altered areas, such as mining, showed similar beta diversity, mainly in the area of bauxite exploration and tailings deposit. Our results indicate that the beta diversity of semiaquatic bugs contribute to the study of altered areas, in addition, could inform conservation policies in streams affected by bauxite mining in the Amazon.
Keywords: Biodiversity; Gerromorpha; Lotic ecosystems; Aquatic insects; Mining